Influence of the coating of edible starch and antioxidant on physiological characteristics of minimally processed yam (Dioscorea sp.) - Furtado, M. C.; De Souza, J. F. [UNESP]; Matos, P. N.; De Araújo, H. G.G.S.; De Jesus, M. S.; Narain, N.; Carnelossi, M. A.G. (International Society for Horticultural Science (ISHS), 2018)
The objective of this study was to evaluate the physiological characteristics of minimally processed yam on the application of edible coating of the starch associated with the addition of ascorbic acid. For this, the minimally processed yam was stored for 12 days at 8±1°C and it underwent five treatments: control - T1; coated only with edible starch - T2; coated only with 1% ascorbic acid - T3; coated with edible starch with 1% ascorbic acid - T4; and coated with 1% ascorbic acid and 1% citric acid - T5. Respiratory rate, evolution of C2H4 and the concentrations of CO2 and ethylene (C2H4) were analyzed. Coated treatments showed the end of the lower storage CO2 concentrations in relation to the treatment in which edible coating was not applied. It was also found that the treatments in which ascorbic acid was incorporated showed higher CO2 release, suggesting its influence as an antioxidant in the respiratory system. Regarding respiratory rate, after finishing the minimal processing were found lower values for treatments with lining, with an average 58% reduction in respiratory rate. After the 4th day, all treatments showed a constant behavior with respect to respiratory rate.
Keywords: Additives; Antioxidants; Gas chromatography; Minimal processing; Yams